Flow and Heat Transfer on a Moving Flat Plate in a Parallel Stream with Constant Surface Heat Flux: A Stability Analysis - Nurul Syuhada, Ismail; Norihan, Md Arifin; Norfifah, Bachok; Norhasimah, Mahiddin (Indian Journal of Science and Technology, 2016)
Numerical solutions for the moving flat plat in a parallel stream with heat flux is to be constant have been studied. By using non-similar transformation, the governing equations be able to reduced to an ordinary differential equation. Then, results of the equations can be solved by shooting method with maple implementation. Numerical results reveal that the velocity ratio parameter λ<0, the non-unique solutions do exist. Then, the analysis of stability is carried out into two non-unique solutions to determine which is more stable between both of the solutions by bvp4c solver in Matlab. From the result of stability analysis, the eigenvalues for the first solution is positive at the same time as second solution is negative.